Rehabilitation of a Large Radicular Cyst of the Mandible Without Using any Bone Substitutes : Case Report - Ahmet Mısır; Birol Ugur; Nilufer Kandemir (Cumhuriyet University, 2014)
The radicular cyst variously known as periapical, apical periodontal, dentoalveolar or root-end cyst is an inflammatory jaw cyst at the apices of teeth with infected and necrotic pulps. A radicular cyst arises from the epithelial residues in the periodontal ligament as a result of inflammation, usually following death of the pulp. Radicular cysts are the most common odontogenic cystic lesions of inflammatory origin and are managed either by surgical enucleation or by marsupialization. We illustrate the possibility of complete healing of a cystic periapical lesion of huge proportion in permanent dentition of a 58 year-old male patient under general anesthesia with conservation of vital structures and without using any bone substitute.